The Reliability and Validity of the Greek Version of the Northwick Park Neck Pain Questionnaire: A Study in Patients with Upper Trapezius Myofascial Trigger Points. - Rentzias, Panagiotis; Stasinopoulos, Dimitrios (Nosileftiki)
Introduction: Myofascial trigger points are a musculoskeletal problem that affect a patient's life. The main symptoms of this common situation are pain, disability, and decrease range of motion of the cervical spine. Many authorities use the Northwick Park Neck Pain Questionnaire to measure the disability caused by trigger points of the upper trapezius muscle. Prior to this study, there was no valid and reliable Greek version of the Northwick Park Neck Pain Questionnaire available. Aim: The purpose of this study was to evaluate the reliability and validity of an adapted Greek version of the Northwick Park Neck Pain Questionnaire. Material and Method: Following the usual steps for cross-cultural adaptation, the validated Northwick Park Neck Pain Questionnaire was administered to 96 patients who were suffering from trigger points in the upper trapezius muscle. All of them completed the questionnaire a second time within 24 hours. Statistical analysis included measurement of internal consistency with Cronbach's α coefficient and reliability with intraclass correlation coefficient to estimate the rank order agreement between the test and the retest questionnaire answers. Also, construct validity was investigated with factor analysis. Results: After results analysis, a Cronbach's α coefficient of 0.926 for the total score was found. Test-retest reliability with intraclass correlation coefficient ranged from 0.933 to 0.970, exhibiting acceptable stability. Construct validity evaluated by factor analysis showed an eigenvalue of 76.745 of total variance, while the factors loading ranged from 0.430 to 0.963. Conclusions: It is concluded that the adapted Greek version of the Northwick Park Neck Pain Questionnaire is valid and reliable and can be used for Greek-speaking patients with active myofascial trigger points of the upper trapezius muscle.